An examination of parental control, peer influence, socio-economic status and career choice among secondary school students in Ibadan (2019)
In recent times, there has been series of problem ranging the world of work. Problems such as career mismatch, un-employability of graduates, downsizing, and the doubt on the quality of procedure for the award of university certificates in the world of work. This activated an examination of parental control, peer influence and socio-economic status as predictors of students’ career choice among secondary school students in Ibadan North Local Government area. This study adopted descriptive survey design of the ex-post facto type. A sample of 288 students was randomly selected. Four reliable measuring scales were used for collection. Pearson product moment correlation and multiple regression analysis were used to analyze the data. The study revealed that there was a significant relationship between parental control, peer influence, socio-economic status and students’ career choice. Multiple regression analysis revealed that parental control, peer influence »and socio-economic status jointly contributed to the prediction of students’ career choice. While it was discovered that the most potent factor was peer influence (Beta = /798, t < 7.934, P<0.01), followed by parental control (Beta =.490, t - 4.167, P<0.01). But socio-economic status (Beta = .052, t = 0.776, P<0.05) is not a potent predictor of students’ career choice. This implies that any change career in adolescent choice is an evidence of increase; in parental control and peer influence. While socioeconomic status is not a significant predictor of students’ career choice. Among others, it was recommended that school counselors should expose students to various career options to save them from being confused by parent and peers. Parents were enjoined to allow their children to choose the career they think it is best based on sound understanding so as to help them fit the work environment and demand of the career. While students also enjoined not to imitate their peers in making their choice of career but to look inward and compare their ability with the demands of their career.